The Effect of Chicken (Gallus gallus domesticus) Eggshell’s Powder towards Wound Healing of Incision Wound on Male Swiss-Webster Mice - Rahman A. Nugraha; Harijadi Pramono; Roro Wahyudianingsih (Universitas Kristen Maranatha, 2016)
Domestic chicken eggshells contain calcium and protein that could be useful in wound healing process. This research was conducted to determine whether domestic chicken eggshells can accelerate wound healing. Twenty one male Swiss-Webster mice with 2 cm incision were divided into 3 groups. Negative control group were given Carboxymethyl cellulose 1% (CMC), positive control group were given feracrylum 1% (FER), and the eggshells group given domestic chicken eggshells powder (KT). Treatment and data mesurement was measured every day until the 7th day. On the 7th day the average length of the wound were analyzed and the skin tissue is taken for microscopic examination. Data analyzed using one-way ANOVA followed by Post Hoc Least Significant Difference (LSD) with p=0,05. On macroscopic examination, there were highly significant differences between KT compared to CMC and highly significant differences between KT compared to FER. the average length of wound on the 7th day on KT 0,63 cm shorter than CMC 1,07 (p=0,000) and FER 0,81 cm (p=0,003). On microscopic examination, the degree of reepithelization on KT groups are severe, moderate for collagen density, fibroblasts density, subepithelial neutrophil density, degree of edema, and mild for angiogenesis. We conclude domestic chicken eggshells powder can accelerate wound healing. Key words: domestic chicken eggshells, incision wound, wound healing